STANDARDIZING HALAL PRODUCTS IMPROVES THE ECONOMY OF ISLAMIC BOARD SCHOOLS IN NURUL HARAMIN NWDI NARMADA - Jalil, Muh. Rabbul (Alif Lam : Journal of Islamic Studies and Humanities, 2024)
This research is motivated by the existence of the Haramain Bakery business unit as one of the business units at the Nurul Haramain Islamic boarding school. The research method used in this research is a qualitative research method. The results of the research show that the management model or form of management in the Haramain Bakery business unit is not neatly structured and recording in financial reports is still done manually. Meanwhile, production management has been carried out independently and regarding halal standardization of Haramain Bakery products, they have received halal certification from the MUI institution. The strategic role of the Haramain Bakery business unit in improving the Islamic boarding school economy is the contribution of the business unit internally to the Islamic boarding school in the form of operational and external costs as a community empowerment institution by creating jobs. Meanwhile, the strategy carried out by the business unit is to increase the Islamic boarding school's economic income in terms of production by adding bread production machines and in terms of marketing by means of Haramain Bakery products being able to compete with well-known products or brands and being able to enter traditional markets.